2000
DOI: 10.1176/appi.ps.51.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Tenure in Supportive Housing for Homeless Persons With Severe Mental Illness

Abstract: Results show that homeless persons with serious mental illness can remain in stable housing for periods of up to five years, supporting the premise that long-term residential stability can be enhanced by providing access to safe and affordable supportive housing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
135
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 18 publications
2
135
0
1
Order By: Relevance
“…There are two general models: The first, supportive housing, includes scattered-site housing with community-based service support and single-room occupancy (SRO) housing (independent housing linked to either communitybased or site-based service support). The second, community residence facilities, includes community residences, long-term treatment facilities, and adult homes (Center for Urban Community Services 1995; Lipton et al 2000). In general, supportive housing emphasizes "normality" in housing in terms of separating services from housing arrangements and giving tenants a choice in their housing arrangements and mental health service regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two general models: The first, supportive housing, includes scattered-site housing with community-based service support and single-room occupancy (SRO) housing (independent housing linked to either communitybased or site-based service support). The second, community residence facilities, includes community residences, long-term treatment facilities, and adult homes (Center for Urban Community Services 1995; Lipton et al 2000). In general, supportive housing emphasizes "normality" in housing in terms of separating services from housing arrangements and giving tenants a choice in their housing arrangements and mental health service regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Lipton et al (2000) found that after one, two, and five years, 75 percent, 64 percent, and 50 percent of the almost 3,000 persons placed had remained in the program across all types of NY/NY housing configurations. Tsemberis (1999) and Tsemberis and Eichenberg (2000) have also found high rates of housing retention by NY/NY recipients, but in addition, found that tenants of one supported scattered-site housing program affiliated with NY/NY had a substantially higher retention rate after five years (88 percent) than other NY/NY supportive housing programs (55 percent).…”
mentioning
confidence: 99%
“…The former finding is consistent with prior studies that have found older HF tenants to have higher rates of housing retention, [11][12][13][14] and may reflect lower levels of substance abuse among older adults, which has been linked to housing failure in prior studies of HF. 11,15 The latter finding may reflect that individuals who have the highest needs and are hardest to place in an initial housing unit continue to experience substantial barriers to housing stability even after they move in to housing.…”
mentioning
confidence: 99%
“…These studies generally provide support for the utility of supportive housing for single mentally ill adults (e.g., Culhane et al 2002;Lipton et al 2000). The use of rental subsidies has been shown to be important for residential stability, across both single adults and families (e.g., Shinn et al 1998).…”
Section: Family Supportive Housingmentioning
confidence: 86%